(untitled) (Atlas Journal of Biology, 2017)
The important crop soybean [Glycine max (L.) Merr.] is cultivated worldwide and the US is its number one exporter. However, farmers face many challenges in cultivating soybeans, including drought and diseases that reduce yields drastically. The root system is very important for plants, including crops, because it receives water and minerals from the soil so that the plant/crop can photosynthesize, grow, and increase its yield. The objective of this study was to grow the ‘MD 96-5722’ by ‘Spencer’ recombinant inbred line (RIL) population (n=86) in the greenhouse under normal (Group I) and drought stress (Group II) conditions, and compare the root length (RL), root surface area (RSA), average root diameter (ARD), and average root volume (ARV) in the two groups of plants. WhinRhizo software was used to measure the root traits and SPSSTM was used to evaluate population performance under normal and drought conditions. JMPTM was used to compare the root traits under normal and drought conditions, and to analyze the correlation between root traits, protein and oil contents. The results showed that there is a huge variation in these traits among the parents ‘MD 96-5722’ and ‘Spencer’, and among their RILs. For Group I plants, the RL of parents and RILs ranged from 20.67 cm to 2,327.88 cm; the RSA ranged from 4.57 cm2 to 1,176.79 cm2; the ARD ranged from 0.38 mm to 4.04 mm; and the ARV ranged from 0.08 cm3 to 47.34 cm3. For Group II plants, the RL of parents and RILs ranged from 15.70 cm to 3,562.42 cm; the RSA ranged from 4.15 cm2 to 829.72 cm2; the ARD ranged from 0.24 mm to 5.74 mm; and the ARV ranged from 0.03 cm3 to 23.67 cm3. It is clear from the results that Group I plants have higher means of RL [572.58 cm vs. 537.33 cm], RSA [201.20 cm2 vs. 165.50 cm2], ARD [3.96 mm vs. 1.45 mm], and ARV [6.31 cm3 vs. 5.61 cm3] compared to Group II plants which demonstrates that drought-stressed plants have reduced overall plant growth and development. However, statistically, these differences were not significant; therefore, further studies with several replicates should be conducted both in the greenhouse and the field in order to determine the effects of drought stress on the ‘MD 96-5722’ by ‘Spencer’ RILs. Moreover, studies of quantitative trait loci (QTL) mapping of the root traits studied here are underway to genetically map QTL for these root traits in this soybean RIL population.